(untitled) - DiNitto, Diana M; Dye, Thomas R (Englewood Cliffs, N.J., 1983)
Includes index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: United States -- Social policy; Hoa Kỳ -- Chính sách xã hội; Public welfare -- United States; Phúc lợi công cộng -- Hoa Kỳ